Bilingual Gifted and Talented Students' Expository Writing: Exploring Academic Language Features in English and Spanish. (December 2020) - Danzak, Robin L.
Bilingual students are underrepresented in gifted and talented (GT) programs, and language/literacy research on these students is scarce. This study examined academic language in expository writing of 65 GT students, including 32 bilinguals, in Grades 4–8. Outcomes at the word, phrase, sentence, and text levels were compared for bilinguals' versus monolinguals' English writing, and bilinguals' English versus Spanish writing. In addition, two students' texts were explored qualitatively. In English, bilinguals and monolinguals did not significantly differ on any measure. Bilinguals scored higher in English than Spanish on most traditional word- and sentence-level measures, were equal in lexical diversity, and varied at the phrase level. English and Spanish writing was similar in content and structure, suggesting transfer of text-level skills. The qualitative assessment highlighted diverse attempts at information condensing and author distance with varying success, again with similar outcomes at the text level.